Unveiling the Impact of Drawing on Digestive System Learning (Lembaga Penelitian dan Pemberdayaan Masyarakat (LITPAM), 2024)
Science education plays a vital role in primary schools, and it is important to improve its quality through innovative teaching and learning methods. This study examines the use of drawing as a strategy to enhance learning about the Digestive System in Year 4 students. The research follows an action research approach, involving one cycle of identifying the problem, implementing the action plan, collecting and analyzing data, and evaluating the outcomes. The participants in this study were 19 students from Mawar Primary School in Brunei Darussalam. Both quantitative (pre- and post-tests) and qualitative (interviews and observations) data were collected and analyzed to assess the effectiveness of the drawing intervention. The findings indicate a positive impact of using drawing as a teaching and learning strategy. However, it should be noted that these results cannot be generalized to all schools.